A randomized, placebo-controlled, double-blinded clinical trial of colchicine to improve vascular health in people living with HIV. (1st June 2021) - Hays, Allison G.; Schär, Michael; Barditch-Crovo, Patricia; Bagchi, Shashwatee; Bonanno, Gabriele; Meyer, Joseph; Afework, Yohannes; Streeb, Valerie; Stradley, Samuel; Kelly, Shannon; Anders, Nicole M.; Margolick, Joseph B.; et al.
Abstract : Objectives: People living with HIV (PWH) experience an increased burden of coronary artery disease (CAD) believed to be related, in part, to an interplay of chronically increased inflammation and traditional risk factors. Recent trials suggest cardiovascular benefits of the anti-inflammatory, colchicine, in HIV-seronegative CAD patients. However, the impact of colchicine on impaired vascular health, as measured by coronary endothelial function (CEF), an independent contributor to CAD, has not been studied in PWH. We tested the hypothesis that colchicine improves vascular health in PWH. Design: This was a randomized, placebo-controlled, double-blinded trial in 81 PWH to test whether low-dose colchicine (0.6 mg daily) improves CEF over 8–24 weeks. Methods: Coronary and systemic endothelial function and serum inflammatory markers were measured at baseline, and at 8 and 24 weeks. The primary endpoint was CEF, measured as the change in coronary blood flow from rest to that during an isometric handgrip exercise, an endothelial-dependent stressor, measured with non-invasive MRI at 8 weeks. Results: Colchicine was well tolerated and not associated with increased adverse events. However, there were no significant improvements in coronary or systemic endothelial function or reductions in serum inflammatory markers at 8 or 24 weeks with colchicine as compared to placebo. Conclusions: In PWH with no history of CAD, low-dose colchicine was well tolerated but did not improve impaired coronary endothelial function, a predictor of cardiovascular events. These findings suggest that this anti-inflammatory approach using colchicine in PWH does not improve vascular health, the central, early driver of coronary atherosclerosis. Abstract : Supplemental Digital Content is available in the text